Lutetium (III) oxide film as passive mode locker device for erbium-doped fibre laser cavity - Harun, Sulaiman Wadi; Baharom, Mohamad Faizal; Ab Rahman, Mohd Fauzi; Abdul Latiff, Anas; P Wang, P Wang (Elsevier Ltd, 2019)
We reported a newly fabricated saturable absorber (SA) namely Lutetium oxide (Lu2O3) thin film for generating a stable and compact mode-locked Erbium-doped fibre laser (EDFL) operating at 1564 nm. The film SA was synthesized by embedding Lu2O3 into polyvinyl alcohol (PVA) host film. By incorporating the film SA along with 200 m long single mode fibre (SMF) into an EDFL cavity, the mode-locked laser with 0.97 MHz repetition rate stably emerged at an increasing pump power, ranging within 145-187mW. The pulse width was measured to be 2.12 ps. The highest pulse energy and peak power were measured as 7.64 nJ and 3.61 kW respectively and were obtained at 187 mW pump power. The fundamental frequency was examined to have a signal to noise ratio (SNR) of 61 dB. These laser performances suggest that the Lu2O3 film SA is feasible for becoming an alternative passive SA in the 1.55 μm region.